2020
DOI: 10.1007/s00234-020-02498-6
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal validation of focal enhancement in intracranial aneurysms as a surrogate marker for aneurysm instability

Abstract: Purpose Circumferential enhancement on MR vessel wall imaging has been proposed as a biomarker of a higher risk of rupture in intracranial aneurysms. Focal enhancement is frequently encountered in unruptured aneurysms, but its implication for risk stratification and patient management remains unclear. This study investigates the association of focal wall enhancement with hemodynamic and morphological risk factors and histologic markers of wall inflammation and degeneration. Methods Patients with an unruptured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 43 publications
6
33
0
4
Order By: Relevance
“…However, we encountered both types of AWE when evaluating the images ( Figure 3 ). Several studies have investigated the relationship between focal AWE and specific hemodynamic factors [ 26 , 27 , 28 ]. The results of these studies revealed that focal AWE occurs at the location of lower wall shear stress, a hemodynamic condition that may be related to a higher risk of aneurysm rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we encountered both types of AWE when evaluating the images ( Figure 3 ). Several studies have investigated the relationship between focal AWE and specific hemodynamic factors [ 26 , 27 , 28 ]. The results of these studies revealed that focal AWE occurs at the location of lower wall shear stress, a hemodynamic condition that may be related to a higher risk of aneurysm rupture.…”
Section: Discussionmentioning
confidence: 99%
“…In their recent paper, Cebral et al reported that low wall shear stress is associated with atherosclerotic and hyperplastic changes in the aneurysmal wall [ 29 ]. In one of the abovementioned studies, Larsen et al provided the results of the histopathological analysis from a subset of patients who underwent microsurgical aneurysm clipping [ 26 ]. The presence of histological inflammatory markers was significantly associated with a larger extent of AWE.…”
Section: Discussionmentioning
confidence: 99%
“…VWE has been linked to vessel‐wall inflammation and associated with a higher risk of rupture 19–22 . 3D T 1 ‐weighted TSE sequences are typically applied for imaging of the vessel wall because they can effectively suppress the signal from flowing blood, providing full brain coverage within an adequate examination time 15, 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Specific hemodynamic conditions, including low wall shear stress (WSS) and low oscillatory shear index (OSI) in the aneurysm, have been associated with a higher risk of rupture 24 . They have been shown to colocalize with contrast‐enhanced wall segments on BB MRI 22 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, risk stratification of patients diagnosed with an unruptured intradural aneurysm is crucial, but optimal management remains controversial. Recently, wall enhancement in intracranial saccular aneurysms on MR vessel wall imaging has been associated with a higher risk for rupture ( 42 46 ) ( Figure 2 ). Experimental studies indicated that flow triggered inflammation in the vessel wall (specifically, macrophage invasion in the vessel wall) may cause formation and growth of intracranial aneurysms ( 47 52 ).…”
Section: Mrimentioning
confidence: 99%